Activation of the Kinin B1 Receptor by Its Agonist Reduces Melanoma Metastasis by Playing a Dual Effect on Tumor Cells and Host Immune Response - Maria, Andrea Gutierrez; Dillemburg-Pilla, Patrícia; Durand, Marina de Toledo; Floriano, Elaine Medeiros; Manfiolli, Adriana Oliveira; Ramos, Simone Gusmão; Pesquero, João Bosco; Nahmias, Clara; Costa-Neto, Claudio M. (Frontiers in Pharmacology, 2019)
Metastatic melanoma is an aggressive type of skin cancer leading half of the patients to death within 8-10 months after diagnosis. Kinins are peptides that interact with B1 and B2 receptors playing diverse biological roles. We investigated whether treatment with B1 receptor agonist, des-Arg9-bradykinin (DABK), has effects in lung metastasis establishment after melanoma induction in mice. We found lower number of metastatic colonies in lungs of DABK-treated mice, reduced expression of vascular cell adhesion molecule 1 (VCAM-1) and increased CD8+ T cells recruitment to the metastatic area compared to animals that did not receive treatment. To understand whether the effects of DABK observed was due to the activation of the B1 receptor in the tumor cells or in the host, we treated wild type (WT) and kinin B1 receptor knockout (B1-/-) mice with DABK. No significant differences in the number of melanoma colonies established in lungs were seen between WT and B1-/- mice, however B1-/- mice presented higher VCAM-1 expression and lower CD8+ T cells infiltration. In conclusion, we believe that activation of kinin B1 receptor by its agonist in the host stimulates the immune response more efficiently, promoting CD8+ T cells recruitment to the metastatic lungs and interfering in VCAM-1 expression. Moreover, treatment with DABK reduced establishment of metastatic colonies by mainly acting on tumor cells, hence this study brings insights to explore novel approaches to treat metastatic melanoma targeting the B1 receptor.